Modelling and efficiency-analysis of wireless power transfer using magnetic resonance coupling - Rehman, M. (Institute of Advanced Engineering and Science, 2017)
Wireless power transfer (WPT) system has got significant attention in recent years due to its applications in consumer electronics, medical implants and electric vehicles etc. WPT is a promising choice in situations, where the physical connectors can be unreliable and susceptible to failure. The efficiency of WPT system decreasing rapidly with increasing air-gap. Many circuit topologies have been employed to enhance the efficiency of the WPT system. This paper presents the modelling and performance analysis of resonant wireless power transfer (RWPT) system using series-parallel-mixed topology. The power transfer efficiency analysis of the model is investigated via circuit theory. S-parameters have been used for measuring power transfer efficiency. Transient analysis is performed to realize the behavior of voltage and current waveforms using advanced design system (ADS) software. The proposed model is tested with two amplitudes i.e. 100 V peak-to-peak and 110 V peak-to-peak at the same frequency of 365.1 kHz. The overall result shows that the series-parallel-mixed topology model has higher efficiency at low coupling factor (K) for both voltage amplitudes. © 2017 Institute of Advanced Engineering and Science. All rights reserved.